Utilizing Blockchain Technology to Prevent Corruption in Indonesia: Between Opportunities and Challenges - Jadida, Hayyina; Shavia, Andina Najma; Izza, Shofi Robiatul (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2025)
Abstract: Corruption is a criminal act that hurts economic, political, and public service development. Corruption remains a challenging issue to eradicate, despite various efforts, due to its complex and systemic nature. Blockchain technology is an innovation that offers transparency, decentralization, and resistance to manipulation, with the potential to serve as a solution in preventing corruption. This research investigates the application of blockchain technology in combating corruption in Indonesia. The research is juridical-normative research with a legislative approach. The collected data was analyzed descriptively. The study results indicate that blockchain technology can enhance accountability and mitigate loopholes for corrupt practices by providing a transparent and decentralized system for recording transactions. However, blockchain implementation still faces challenges, such as limited infrastructure, immature regulations, and a lack of understanding of this technology. Therefore, supportive policies, investment in digital infrastructure, and increased technological literacy are needed to ensure optimal use of blockchain in preventing corruption crimes.